2002
DOI: 10.1103/physrevb.65.132506
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the electron density of states in superconductingMgB2disordered by neutron irradiation:11

Abstract: NMR line shift and nuclear spin-lattice relaxation rate T −1 1 of 11 B and 25 Mg were measured in superconducting MgB2 (T ons c =38K) structurally disordered by nuclear reactor neutrons up to the fluence of thermal neutrons Φ = 1 • 10 19 cm −2 . The temperature of superconducting transition was shifted down to T ons c,irrad =7K under irradiation. The change due irradiation in the partial electron density of states (DOS) at the Fermi energy of boron and magnesium were traced by taking into account that T −1 1 o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 11 publications
2
24
1
Order By: Relevance
“…The accuracy of the K values were estimated to be ±8 ppm, where the uncertainty results from an incomplete reduction of the strong dipolar interaction in the MAS experiment, mainly between the boron nuclei. These values of K are much smaller than those observed in MgB 2 , where K( 11 B) = 100 ppm [36] and in YNi 2 B 2 C, where K( 11 B) ≈ 400 ppm [37] (both values are for room temperature). This comparison indicates that the values for the densities of states (DOS) at the Fermi level for the boron sites are much lower than those in the borides mentioned above.…”
Section: Knight Shiftscontrasting
confidence: 57%
“…The accuracy of the K values were estimated to be ±8 ppm, where the uncertainty results from an incomplete reduction of the strong dipolar interaction in the MAS experiment, mainly between the boron nuclei. These values of K are much smaller than those observed in MgB 2 , where K( 11 B) = 100 ppm [36] and in YNi 2 B 2 C, where K( 11 B) ≈ 400 ppm [37] (both values are for room temperature). This comparison indicates that the values for the densities of states (DOS) at the Fermi level for the boron sites are much lower than those in the borides mentioned above.…”
Section: Knight Shiftscontrasting
confidence: 57%
“…Previous Knight shift calculations for 11 B in MgB 2 [6] and AlB 2 [11] have indicated that positive contributions prevail and positive values of K are expected. This positive sign of K is confirmed by Gerashenko et al [19] who have analyzed K ( 11 B) in MgB 2 where, in contrast to earlier calculations [6], substantial K orb is permitted. Indeed, the positive shift with MgB 2 has been observed experimentally but found to be negative with AlB 2 [11].…”
Section: Resultssupporting
confidence: 85%
“…10 have found that in the normal state (T = 50 K) ν Q obtained from magnetic-field dependence of the NMR frequency shift is equal to 1100±150 kHz. However, ν Q (FWHM) determined through the relation ν Q (FWHM) = 1.3856(ν 0 ∆ν) 1/2 , where ∆ν is the width between the peak and shoulder of NMR spectrum, is equal to 835 kHz 10 , in close agreement with the ν Q values found in other NMR experiments 8,9 (see Table 2 below). TDPAC investigation of these phases 11 .…”
Section: Introductionsupporting
confidence: 87%
“…A recent 11 B NMR study 7 has revealed an exponential temperature dependence of the nuclear relaxation rate 1/T 1 in the superconducting (SC) state, with a relatively large SC gap of 2∆/k B T c ~ 5 implying strong-coupling s-wave superconductivity in this system. Other 11 B NMR studies 8,9 of MgB 2 have provided important information on the local electronic state of the boron site by measuring the 11 B quadrupole coupling constant ν Q = eQV zz /h that can be evaluated theoretically from first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%